2010
DOI: 10.1161/circresaha.109.202176
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-133a Protects Against Myocardial Fibrosis and Modulates Electrical Repolarization Without Affecting Hypertrophy in Pressure-Overloaded Adult Hearts

Abstract: Rationale: MicroRNA (miR)-133a regulates cardiac and skeletal muscle differentiation and plays an important role in cardiac development. Because miR-133a levels decrease during reactive cardiac hypertrophy, some have considered that restoring miR-133a levels could suppress hypertrophic remodeling. Objective: To prevent the "normal" downregulation of miR-133a induced by an acute hypertrophic stimulus in the adult heart. Methods and Results: miR-133a is downregulated in transverse aortic constriction (TAC) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
273
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(288 citation statements)
references
References 48 publications
14
273
0
1
Order By: Relevance
“…Both miR-30 and miR-133 condition the protein level of CTGF, and their decrease after myocardial damage leads to fibrosis and conduction anomalies (10,46). In agreement with these findings reported by other authors, we found that the T3-dependent miRNA modulation was accompanied by decreased MMP-2 and CTGF expression 3 d post-I/R.…”
Section: Disclosuresupporting
confidence: 92%
“…Both miR-30 and miR-133 condition the protein level of CTGF, and their decrease after myocardial damage leads to fibrosis and conduction anomalies (10,46). In agreement with these findings reported by other authors, we found that the T3-dependent miRNA modulation was accompanied by decreased MMP-2 and CTGF expression 3 d post-I/R.…”
Section: Disclosuresupporting
confidence: 92%
“…So far, there seems to be about 150-200 miRNAs expressed in the cardiovascular system. Many of these miRNAs are dynamically regulated in response to acute cardiac stress and in some cases during long-term compensatory response of the heart to a chronic injury or hemodynamic overload 13,14 . Therefore, there is growing evidence that the expression of miRNAs is an important part of the mechanism of response to acute stress of the heart, contributing both to cardiac homeostasis and to the heart disease.…”
Section: Micrornas and The Cardiovascular Systemmentioning
confidence: 99%
“…In a recent study, the expression of miR-133 was induced in a rat model subjected to acute hypertrophic stimulus. Although the weight of the heart has not been standardized, other aspects of hypertrophy, such as apoptosis and fibrosis were restored to basal levels 14 .…”
Section: Micrornas In Cardiac Hypertrophy and Heart Failurementioning
confidence: 99%
“…They are also upregulated during cardiac hypertrophy and failure, and have been implicated in arrhythmogenesis [56]. The downregulation of miR-133 during cardiac hypertrophy is also associated with a decrease in K cnip2, the I to,f accessory subunit, albeit via an indirect mechanism, and is accordingly, responsible for prolongation of the QT interval [57]. Taken together, miR-1 and miR-133 are multifaceted molecules involved in hypertrophic and ischemic heart by targeting of a spectrum of mRNAs.…”
Section: Arrhythmiamentioning
confidence: 99%